2017
DOI: 10.18632/oncotarget.17997
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and its analogs: Potential avenues for prostate cancer management

Abstract: Epidemiological studies have demonstrated a relationship between cancer incidence and dietary habits. Especially intake of certain essential nutrients like vitamins has been shown to be beneficial in experimental studies and some clinical trials. Vitamin K (VK) is an essential nutrient involved in the blood clotting cascade, and there are considerable experimental data demonstrating its potential anticancer activity in several cancer types including prostate cancer. Previous in vitro and in vivo studies have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 167 publications
0
33
0
1
Order By: Relevance
“…It is possible that synergistic effect of other nutrients in this pattern, cause the significant effect of folate on reducing the risk of prostate cancer, that is completely in line with our hypothesis based on the effect of interactions between nutrients and the predominance of the effect of a higher consumption of nutrients that exhibit behavioural coexistence. Inverse association between green leafy and cruciferous vegetables (the main source of vitamin K1) and prostate cancer risk have been reported in several studies (Hardin et al, 2011;Dasari et al, 2017). Also, the protective effect of vitamin K2 (another form of vitamin K that found in animal product) reported in one cohort study (Nimptsch et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is possible that synergistic effect of other nutrients in this pattern, cause the significant effect of folate on reducing the risk of prostate cancer, that is completely in line with our hypothesis based on the effect of interactions between nutrients and the predominance of the effect of a higher consumption of nutrients that exhibit behavioural coexistence. Inverse association between green leafy and cruciferous vegetables (the main source of vitamin K1) and prostate cancer risk have been reported in several studies (Hardin et al, 2011;Dasari et al, 2017). Also, the protective effect of vitamin K2 (another form of vitamin K that found in animal product) reported in one cohort study (Nimptsch et al, 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, the ''plant source" pattern (loaded heavily on potassium, Vitamin K, total folate, beta-carotene and lutein) was negatively associated with risk of prostate cancer. Numerous studies have shown the protective effects of vitamin K and carotenoids consumption on prostate cancer risk (Nimptsch et al, 2008;Nimptsch et al, 2015;Dasari et al, 2017), However there is conflicting evidence regarding folate intake and prostate cancer risk. Some Studies found no association between dietary and total folate intake and prostate cancer risk, while other studies reported that higher blood folate levels increased prostate cancer risk (Figueiredo et al, 2009;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It's known that VK3 exhibits potent anticancer effects in various cancers such as breast, hepatic, bladder, pharyngeal, and blood cancers [34]. VK3 promoted the ROS production which disrupted the intracellular calcium homeostasis, depleted cellular thiol levels, increased lipid peroxidation and finally killed the cancer cells [35]. Early in 2003 it was reported that VK3 may have antitumor effect on ovarian cancer [36].…”
Section: Discussionmentioning
confidence: 99%
“…Накоплены данные, свидетельствующие о противоопухолевых эффектах витамина K, его роли при некоторых онкологических заболеваниях, таких как гепатоцеллюлярная карцинома, рак поджелудочной и предстательной желез [27,28]. В работе 2017 г. s. Dahlberg et al описали ряд патогенетических механизмов действия витамина K на опухолевые клетки: связывание с рецептором sXR приводит к подавлению роста опухоли путем снижения экспрессии протоонкогена с-Мус4, что сопровождается замедлением клеточной пролиферации; уменьшение воспалительных сигналов, потенцирующих развитие опухолевого процесса за счет активирования ядерного фактора каппа B (NF-κB); подавление опухолевого роста путем воздействия на сигнальные пути митоген-активируемых протеинкиназ; блокирование клеточного цикла путем подавления циклина D1; индукция апоптоза путем воздействия на каспазу-3; синтез цитотоксических актив ных форм кислорода [29].…”
Section: эффекты витамина Kunclassified